Personality of Central Jawa Finswimming Athlete to Bifins Relay - Sungkowo Sungkowo; Tandiyo Rahayu; Agus Kristiyanto; Donny Wira Yudha Kusuma; Heny Setyawati (Universitas Negeri Semarang, 2022)
The role of psychology as an intermediary between players' physical, technical and tactical abilities, psychology is one of the keys to successful performance because of its influence on the competitive success of athletes. The research method used is a survey where the researcher describes the results of the Myers Briggs type indicator. The results showed that 4 athletes before filling out the questionnaire type myers briggs indicator, with personality data: Gienna Oceani Prasetyo with MBTI scale Introvert 87% - Extrovert 13%, Sensing 87% - Intuition 13%, Thinking 40% - Feeling 60%, Judging 80 % - Perceiving 20% ​​then get ISFJ personality type, Ashifa Helpa Ashuroh with MBTI scale Introvert 67% - Extrovert 33%, Sensing 60% - Intuition 40%, Thinking 53% - Feeling 47%, Judging 60% - Perceiving 40% then get ISTJ personality type, Winda Santika Wardani with MBTI scale Introvert 60% - Extrovert 40%, Sensing 53% - Intuition 47%, Thinking 53% - Feeling 47%, Judging 13% - Perceiving 87% then get the ISTP personality type, Mustikaning Song with MBTI scale Introvert 80% - Extrovert 20%, Sensing 67% - Intuition 33%, Thinking 53% - Feeling 47%, Judging 67% - Perceiving 33% then get the ISTJ personality type.